The Role of Islamic Boarding School Management in Shaping Students’ Discipline and Responsibility Character - Anwar Hasanudin; Mahbub Junaidi (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
Character education is an important component in building a moral, disciplined, and responsible generation. Islamic boarding schools have a strategic role in this process through a student management system designed as a model for character development. This study aims to determine: (1) the implementation of the role of the Tanwirul Qulub Islamic Boarding School administrators in shaping the disciplined and responsible character of students; and (2) the supporting and inhibiting factors in the implementation of this role. This study uses a descriptive qualitative method of field research, with data collection techniques through observation, interviews, and documentation. Data analysis is carried out through the process of data reduction, data presentation, and drawing conclusions, as well as testing the validity of the data using triangulation techniques and sources. The results of the study indicate that the role of administrators is very important in shaping the disciplined and responsible character of students through programs: night roll call, point system, and student summons. Supporting factors in the implementation of these roles include support from the caretakers and supervisors of the boarding school, a clear and consistent system of rules and regulations, and commitment and solidarity among administrators. Meanwhile, the inhibiting factors faced by the management include differences in the students' backgrounds, the management's busy schedule in formal academic activities and lectures, and negative influences from peers which make it difficult for the students to receive guidance. Keywords: Role of Management, Disciplinary Character, Responsibility, Students